Hubungan Spiritualitas dengan Keputusasaan pada Remaja dengan HIV/AIDS - Sumirta, I Nengah; Utami Budiari, Ni Putu; Harini, I Gusti Ayu; Candra, I Wayan; Ari Kresna Dewi, Ni Luh Gede (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2025)
HIV/AIDS is an infectious disease that attacks the immune system, resulting in a significant decline in physical health and triggering vulnerability to psychological problems, such as hopelessness. Despair can lead to decreased treatment adherence, which may worsen physical conditions and accelerate disease progression. The aim of this study was to analyze the relationship between spirituality and hopelessness in adolescents with HIV/AIDS. This type of quantitative research uses a correlational design with a cross-sectional approach. The sample size of 63 people was collected using purposive sampling technique. Data collection instruments used the Daily Spiritual Experience Scale (DSES) and the Beck Hopelessness Scale (BHS). Data analysis using Spearman's Rank Correlation Coefficient test. The results showed that 30 people (47,6%) had low spirituality, 28 people (44,4%) had moderate spirituality, 5 people (7,9%) had high spirituality and 4 people (6,3%) experienced mild hopelessness, 31 people (49,2%) experienced moderate hopelessness, 28 people (44, 4%) experienced moderate hopelessness and there was a relationship between spirituality and hopelessness with a p-value of 0.000 (p-value 0,005), correlation coefficient value of -0,664, strong correlation and negative direction which means the higher the spirituality, the lower the hopelessness. The inclusion of a spiritual approach in psychosocial interventions for adolescents with HIV/AIDS is recommended as a relevant strategy to reduce the risk of despair, strengthen psychological resilience, and enhance the overall quality of life of adolescents living with HIV/AIDS.